Validation of the Argentine version of the Memory Binding Test (MBT) for Early Detection of Mild Cognitive Impairment - Román, Fabián (2016)
Background: “Forgetfulness” is frequent in normal aging and characteristic of the early stages of dementia syndromes. The episodic memory test is central for detecting amnestic mild cognitive impairment (MCI). The Memory Binding Test (MBT) is a simple, easy and brief memory test to detect the early stage of episodic memory impairment. Objective: To validate the Argentine version of the MBT in a Latin American population and to estimate the diagnostic accuracy as a tool for early detection of MCI. Methods: 88 subjects (46 healthy controls and 42 patients with amnestic MCI) matched for age and educational level were evaluated by an extensive neuropsychological battery and the memory binding test. Results: A significantly better performance was detected in the control group; all MBT scales were predictive of MCI diagnosis (p<.01). The MBT showed high sensitivity (69%) and high specificity (88%), with a PPV of 93% and a NPV of 55% for associative paired recall. A statistically significant difference (c2 =14,164, p<.001) was obtained when comparing the area under the curve (AUC) of the MBT (0.88) and the MMSE (0.70). Conclusion: The Argentine version of the MBT correlated significantly with the MMSE and the memory battery and is a useful tool in the detection of MCI. The operating characteristics of the MBT are well suited, surpassing other tests commonly used for detecting MCI.